Open Radio Access Network (O-RAN): Empowering the Future of Telecommunication - G S, Dr. Mamatha; Anusha, G (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Massive Internet of Things (IoT) networks and cutting-edge innovations like self-driving cars and high-speed games require a flexible network that can accommodate all of these applications. Due to different quality of service (QoS) needs, current radio access networks (RANs) are unable to support such diverse applications. Therefore, it is believed that the Open Radio Access Network (O-RAN) is the most practical substitute for next-generation RAN. The evolution of RAN as well as potential designs and traits of the most promising O-RAN (next-generation RAN) are covered in this article. This study focuses on the peculiarities of the RAN design as it has changed throughout time. The deployment of O-RAN also examines a number of implementation challenges and potential opportunities.